The Impact Of Human Capital On Nigeria’s Economic Growth - Bachama, Yusufu Nigel; Hassan, Aisha Adamu; Ibrahim , Bello (European Scientific Journal, ESJ, 2021)
Despite abundant evidence at microeconomic level, the role of human capital in promoting economic growth and development has not been well documented at the macroeconomic level – specifically in developing countries. This paper seeks to examine the role of human capital on economic growth in Nigeria using time series data covering the period from 1970-2019. The data are sourced from Central Bank of Nigeria (CBN) statistical bulletin and World Development Indicators of the World Bank. The data are analyzed using Autoregressive Distributed Lag model (ARDL). The study reveals that expenditure on health and education are found to be positively and significantly related with economic growth both in the short-run and long-run. However, labor negatively impact on economic growth and it was found to be significant. Again, trade openness and inflation are insignificant in explaining economic growth in this paper. Thus, the paper recommends that, Nigerian government should focus on improving the educational and health sector. Meaning that, huge amount of government budgetary allocation should be directed toward educational and health sector. So also, government should create more jobs opportunities (through skills acquisitions/ vocational training) to minimize the unemployment rate in the country.